2009
DOI: 10.1136/vr.165.12.335
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of tuberculosis caused by Mycobacterium bovis in golden Guernsey goats in Great Britain

Abstract: An outbreak of caprine tuberculosis caused by Mycobacterium bovis was disclosed in June 2008, affecting goats of the golden Guernsey breed kept on 10 separate smallholdings in south-west Wales and the west of England. Following the initial diagnosis at postmortem examination, 30 goats that reacted positively to the single intradermal comparative cervical tuberculin (SICCT) test, together with five in-contact animals, were euthanased and subjected to postmortem examination and mycobacterial culture. Spoligotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 22 publications
(38 reference statements)
0
51
0
1
Order By: Relevance
“…A high challenge dose (higher than 10 6 CFU) by nonnatural routes (such as intravenous or subcutaneous) may lead to systemic dissemination of infection, with lesions that are not representative of natural field cases (40). Using a relative low challenge dose of 1.5 ϫ 10 3 CFU by the endobronchial route, we have been able to reproduce typical granulomatous caseous necrotizing lesions in the lung and lung-associated LN in 11 out of 11 experimentally infected goats, resembling those observed in naturally infected goats (12,31), and as seen sometimes in natural cases, the majority of our Infected 572…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A high challenge dose (higher than 10 6 CFU) by nonnatural routes (such as intravenous or subcutaneous) may lead to systemic dissemination of infection, with lesions that are not representative of natural field cases (40). Using a relative low challenge dose of 1.5 ϫ 10 3 CFU by the endobronchial route, we have been able to reproduce typical granulomatous caseous necrotizing lesions in the lung and lung-associated LN in 11 out of 11 experimentally infected goats, resembling those observed in naturally infected goats (12,31), and as seen sometimes in natural cases, the majority of our Infected 572…”
Section: Discussionmentioning
confidence: 77%
“…In natural infections, TB in goats, as in cattle, is primarily a lower respiratory tract disease, with lesions in the lungs and associated lymph nodes (LN). Occasionally, tuberculous lesions may also be found in the upper respiratory tract lymph nodes and other organs, like the spleen, liver, or mesenteric lymph nodes (12,31). Histologically, the lesions are similar to those observed in cattle and humans.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Most commonly in goats, the cough is usually seen as a chronic cough which is unresponsive to treatment and may be accompanied by gradual loss of weight and sometimes diarrhoea (Aranaz et al, 2003). The Predilection site for tuberculosis in goats is the lower respiratory tract and the associated lymph nodes (Daniel et al, 2009). Epidemiological studies have indicated that tuberculosis in goat and sheep has a wide global distribution, being reported in several countries of the world including New Zealand, Sudan, Spain, Nigeria, the United Kingdom, Italy, Algeria and Ethiopia (Aranaz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Caprine TB is an emerging zoonotic disease in many European countries [1,2]. Vaccination could be taken into consideration as an alternative to test-and-slaughter strategy for long-term TB control in livestock [3].…”
Section: Introductionmentioning
confidence: 99%